Isolation of Klebsiella Pneumoniae from an Hepatic Inflammatory Pseudotumour - Dickran K Malatjalian; John Morris; Audley Bodurtha (Canadian Journal of Gastroenterology)
lnflammatory pseudotumours of the liver are rare, solid mass lesions (often mistaken for malignancy) and although inflammatory in nature, are obscure in etiology and pathogenesis. An hepatic inflammatory pseudotumour is presented in which cultures obtained from the lesion intraoperatively grew Klebsiella pneumoniae. This is the first case of an hepatic inflammatory pseudotumour in which a microorganism has been identified. The isolation of K pneumoniae suggests that inflammatory pseudotumours may arise from a low grade infection with chronic inflammatory tissue response.